250 tips, techniques, and trade secrets for potters - Atkin, Jacqui (Barron's, 2009)
Describes the full range of available clays and their individual qualities, as well as necessary tools and equipment; presents easy-to-follow directions for fashioning pottery; and augments instruction with captioned, step-by-step photos, illustrations, and sidebars featuring troubleshooting tips with solutions to problems that often arise in the process of making pottery. This essential reference book also covers topics such as developing design concepts, from sketch pad to finished piece; slabbing, pinching, coiling, throwing, turning, and mold-making, using various clays; and creating surface decoration, with attention to colors, textures, and glazing.